Global Forest Governance and Climate Change Interrogating Representation, Participation, and Decentralization (Palgrave Studies in Natural Resource Management, 2018)
This edited collection assesses governance in forestry programmes and projects, including REDD+ governance. It examines political representation, participation and decentralisation in forest governance, providing insight as to how forest governance arrangements can be responsive to the socio-economic interests of local people and communities who live adjacent to and depend on forests. Global Forest Governance and Climate Change argues that inclusive complementary representation of local communities is required for strong participatory processes and democratic decentralisation of forest governance. Responsiveness to local people's socio-economic interests in forestry initiatives require paying attention to not just the hosting of participatory meetings and activities, but also to the full cast of appointed, self-authorized, and elected representative agents that stand, speak, and act for local people. This book will be of interest to students and academics across the fields of climate change governance, forestry, development studies, and political economy. It will also be a useful resource for policy makers and practitioners responsible for forestry and climate change initiatives.